Geomorphosites and geotourism in Bucharest city center (Romania) - Comănescu, Laura; Nedelea, Alexandru; Stănoiu, Gabriel (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2017)
The present paper aims at inventorying the geomophosites in Bucharest as well as introducing geotouristic itineraries that take into account the long-time developed high value cultural heritage of the area. The process included several stages: studying Bucharest’s relief and cultural- historical elements with tourist value from existing bibliography, cartographic methods (aerial photos and different editions of topographic maps), as well as the information gathered from field investigations; identifying and inventorying geomorphosites, assessing the population’s opinion about geoheritage (geomorphosites) and its capitalization in tourism activities, 100 questionnaires were applied; creating geotouristic itineraries and later promoting them. The most valuable and representative geomorphosites identified are: on Colentina Valley (the Plumbuita, Ostrov, Dobroeşti and Pantelimon hills) (aren’t located in the study area), on Dâmboviței Valley (Cotroceni, Șerban Vodă, Mitropoliei, Spirii, Filaret and Arsenal hills, Țăcăliei, Procopoaiei, University terraces, Dâmbovița Meadow). The authors suggest two geotouristic itineraries that emphasize the relationship between the scientific, cultural, and historic elements as well as the human-nature report within the urban area.
Keywords: geomorphosites; geotouristic itineraries; Bucharest; Romania